Identification of soil-dwelling predators of tick nymphs (Acari: Ixodidae) by stable isotope labeling - Vinogradov, Dmitry D; Smagin, Alexander S; Belova, Oxana A; Tsurikov, Sergey M; Karganova, Galina G; Tiunov, Alexei V (Journal of medical entomology, 2024)
Ticks (Family Ixodidae) spend most of their life cycle as immature stages in the soil and litter, and as any other soil invertebrates, are likely to be controlled top-down by soil-dwelling predators. To date, the ability of soil invertebrate predators to control ixodid tick population remains little known, partly due to methodological difficulties. In the current study, we developed and successfully tested a novel method of labeling live Ixodes ricinus (L., 1758) (Ixodida: Ixodidae) nymphs with a 15N isotope label. Labeled ticks were used in a small-scale 8-day-long microcosm experiment to reveal soil predators attacking nymphs. Only a small fraction (4.1% of all samples) of soil generalist predators preyed upon nymphs. A strong 15N label was found in 5 predator species, namely 2 spiders (Pachygnatha listeri Sundevall, 1830, Tetragnathidae and Ozyptila sp., Theridiidae), 2 gamasid mites (Pergamasus beklemischevi Sellnick, 1929 and Pergamasus quisquiliarum [Canestrini, 1882], Parasitidae), and 1 staphylinid beetle (Geostiba circellaris [Gravenhorst, 1806], Staphylinidae). The isotopic labeling can be a useful tool in revealing a range of invertebrate predators that can control tick populations in soil.
Keywords: Animals; Nymph; Ixodes; brouci; zvířata; izotopové značení; půda; Soil; klíště; Coleoptera; Isotope Labeling; Ixodidae; nymfa